Atomic Layer Deposition: 2D Transition Metal Dichalcogenide Thin Films Obtained by Chemical Gas Phase Deposition Techniques (Adv. Mater. Interfaces 3/2019). Issue 3 (8th February 2019) - Park, Gyu‐Hyeon; Nielsch, Kornelius; Thomas, Andy
Abstract : Ultrathin 2D transition metal dichalcogenide (TMD) thin films have attracted much attention due to their very good electrical, optical, and electrochemical properties. Here, the recent progress in 2D TMD thin films is reviewed and the current applications of these materials fabricated by chemical vapor deposition and atomic layer deposition are surveyed. More details are in article number1800688 by Gyu‐Hyeon Park, Kornelius Nielsch, and Andy Thomas.